Photoinitiated Polymerization of Cationic Acrylamide in Aqueous Solution: Synthesis, Characterization, and Sludge Dewatering Performance - Huaili Zheng; Yi Liao; Meizhen Zheng; Chuanjun Zhu; Fangying Ji; Jiangya Ma; Wei Fan (The Scientific World Journal)
A copolymer of acrylamide (AM) with acryloyloxyethyl trimethyl ammonium chloride (DAC) as the cationic monomer was synthesized under the irradiation of high-pressure mercury lamp with 2,2-azobis(2-amidinopropane) dihydrochloride (V-50) as the photoinitiator. The compositions of the photoinduced copolymer were characterized by Fourier transform infrared spectra (FTIR), ultraviolet spectra (UV), and scanning electron microscope (SEM). The effects of 6 important factors, that is, photo-initiators concentration, monomers concentration, CO(NH2)2 (urea) concentrations, pH value, mass ratio of AM to DAC, and irradiation time on the molecular weight and dissolving time, were investigated. The optimal reaction conditions were that the photo-initiators concentration was 0.3%, monomers concentration was 30 wt.%, irradiation time was 60 min, urea concentration was 0.4%, pH value was 5.0, and mass ratio of AM to DAC was 6 : 4. Its flocculation properties were evaluated with activated sludge using jar test. The zeta potential of supernatant at different cationic monomer contents was simultaneously measured. The results demonstrated the superiority of the copolymer over the commercial polyacrylamide as a flocculant.